Assessment of Endothelial Dysfunction in Patients with Covid-19 Based on Chronic Heart Failure and its Significance in the Effectiveness of the Treatment (Texas Journal of Medical Science, 2022)
This article discusses the importance of endothelial dysfunction in patients with COVID-19 due to chronic heart failure and the effectiveness of its treatment.